2022
DOI: 10.1098/rsob.220151
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal transcript levels and metabolomics analyses reveal metabolic changes associated with intrauterine growth restriction and sex

Abstract: The metabolic changes associated with intrauterine growth restriction (IUGR) particularly affect the liver, which is a central metabolic organ and contributes significantly to the provision of energy and specific nutrients and metabolites. Therefore, our aim was to decipher and elucidate the molecular pathways of developmental processes mediated by miRNAs and mRNAs, as well as the metabolome in fetal liver tissue in IUGR compared to appropriate for gestational age groups (AGA). Discordant siblings representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Our findings indicate that alterations in fat and sugar metabolism occur as early as GD60 in L foetuses, as shown by differences in the expression of UCP3, a protein involved in transport of fatty acids from/ into the mitochondria 41 , APOB, a major lipoprotein component, and the glycolytic enzyme, ALDOB. These results align with previous reports of higher levels of plasma cholesterol as well tissue fatty acid synthesis and ALDOB expression in low-weight pig foetuses already by GD63 13,42 . Moreover, our results suggest that lipid usage by muscle markedly increases in growth-restricted foetuses during the second half of gestation, as suggested by much higher expression levels of APOB and the triacylglycerol lipase, PNPLA3, in L than AW piglets by GD90.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings indicate that alterations in fat and sugar metabolism occur as early as GD60 in L foetuses, as shown by differences in the expression of UCP3, a protein involved in transport of fatty acids from/ into the mitochondria 41 , APOB, a major lipoprotein component, and the glycolytic enzyme, ALDOB. These results align with previous reports of higher levels of plasma cholesterol as well tissue fatty acid synthesis and ALDOB expression in low-weight pig foetuses already by GD63 13,42 . Moreover, our results suggest that lipid usage by muscle markedly increases in growth-restricted foetuses during the second half of gestation, as suggested by much higher expression levels of APOB and the triacylglycerol lipase, PNPLA3, in L than AW piglets by GD90.…”
Section: Discussionsupporting
confidence: 93%
“…Developmental programming as an adaptive response to IUGR in the pig is associated with widespread transcriptional and epigenetic dysregulation in foetal muscle, involving a myriad of developmental, tissue injury (i.e. associated with inflammation and immunity) and metabolic pathways, as shown by us and others 9,[12][13][14] . Studies in sheep, another commonly used (experimentally induced) large animal model of IUGR, have shown that an increased inflammatory milieu in growth-restricted foetuses is induced by a catecholamine-mediated stress response to reduced resource availability, including hypoxia, to body tissues 15 .…”
mentioning
confidence: 88%
“…The snowball Microarray (Affymetrix) with 47,880 probe sets representing 17,964 annotated genes was used to determine the expression profile. Analysis of the microarray data was performed using the Expression Console 1.3.1.187 software platform (Affymetrix) to translate intensities of chip-spots into values for the expression of transcripts represented by probe-sets as described in our previous study [ 53 ]. Background correction, normalization, and summarization was performed using the Robust Multiarray Average (RMA) algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…DEGs were selected for qPCR validation using a 48 × 48 Dynamic array with an integrated fluidic circuit (IFC) on the BioMark HD Real-time PCR System (Fluidigm, South San Francisco, CA, USA). Specific target amplification (STA) was performed according to the manufacturer’s recommendations and according to our previous study [ 53 ]. Pre-amplification sample mixtures were prepared using PreAmp Master Mix (Fluidigm PN 1,005,581) containing 1.25 µL of cDNA, 1 µL PreAmp Master Mix, and 0.5 µL Pooled Delta Gene Assay Mix (500 nM) containing DNA-suspensions buffer and primers mixes in 5 µL total volume.…”
Section: Methodsmentioning
confidence: 99%